2000
DOI: 10.1007/s002469910023
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Manifestations in Patients with HLA B27-Associated Juvenile Arthritis

Abstract: Cardiac involvement is common in adult patients with the presence of HLA B27 with or without the HLA B27-associated spondyloarthropathy ankylosing spondylitis. Most patients with juvenile spondyloarthropathy, which begins at age 16 or younger, do not have spinal involvement and there are only few reports of cardiac involvement. This study sought to assess the prevalence of carditis in patients with HLA B27-associated juvenile arthritis (B27-JA). In a controlled study, 40 patients with B27-JA, among them only 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 28 publications
2
12
2
2
Order By: Relevance
“…Our study is in agreement with the studies of Oguz et al [9] and Bharti et al [19]. Huppertz et al [22] reported that late diastolic Xow velocity was signiWcantly increased in patients with HLA B27-associated JIA at the termination of exercises. This is in contrast to our results where we noted diastolic dysfunction at rest.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Our study is in agreement with the studies of Oguz et al [9] and Bharti et al [19]. Huppertz et al [22] reported that late diastolic Xow velocity was signiWcantly increased in patients with HLA B27-associated JIA at the termination of exercises. This is in contrast to our results where we noted diastolic dysfunction at rest.…”
Section: Discussionsupporting
confidence: 95%
“…This is consistent with results of Ozer et al [8] and Bernstein et al [21], who reported the occurrence of pericarditis in 30 and 36%, respectively, of their series of JIA patients without any clinical evidence of pericarditis. In contrast to previous results, Oguz et al [9], Bharti et al [19] and Huppertz et al [22] reported the absence of pericardial eVusion in their JIA series. Valvular involvement is a rare but serious complication of JIA.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Echocardiographic detection of early cardiac involvement in juvenile rheumatoid arthritis (RA) was shown previously in one case series [17]. Systolic and diastolic functions of the left ventricle were studied echocardiographically in children with JIA in several studies [1,4,13,19], but no studies have evaluated right-ventricular (RV) functions with echocardiography in children with JIA. Pulsed tissue Doppler tissue (TDI) of the velocity of tricuspid annular motion is a new, rapid, and noninvasive method for evaluating RV functions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Ainsi, les auteurs concluaient à la non-corrélation entre l'IA et l'HLA B27 en l'absence de spondylarthrite. Huppertz et al ont analysé les atteintes cardiaques de 40 arthrites juvéniles à l'aide d'une écho-graphie cardiaque systématique [41]. Quatre patients HLA B27 positif avaient une IA.…”
Section: Troubles De La Conductionunclassified